2018
DOI: 10.1007/s10787-018-0519-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of adiposity and related metabolic disturbances by polyphenol-rich extract of Boswellia serrata gum through alteration of adipo/cytokine profiles

Abstract: Boswellia serrata is as effective as orlistat in preventing obesity, hyperlipidemia, steatosis and insulin resistance. These actions may be mediated by suppression of food intake and decrease levels of TNF-α, IL-1β and leptin resistance along with increasing adiponectin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Many studies suggested that the pathological hallmarks of type 2 diabetes-related dementia are tau-related neurofibrillary tangles and not amyloid-beta plaques [ 59 – 61 ]. Intervention for AD may be more successful through inhibiting insulin resistance and abnormal GSK-3β activity [ 7 , 43 , 60 , 61 ]. PCDE in the present study reduced insulin resistance and hippocampal GSK-3β activity and improved all toxic consequences features of AD that have been detected in the T2D animal model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies suggested that the pathological hallmarks of type 2 diabetes-related dementia are tau-related neurofibrillary tangles and not amyloid-beta plaques [ 59 – 61 ]. Intervention for AD may be more successful through inhibiting insulin resistance and abnormal GSK-3β activity [ 7 , 43 , 60 , 61 ]. PCDE in the present study reduced insulin resistance and hippocampal GSK-3β activity and improved all toxic consequences features of AD that have been detected in the T2D animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of peripheral insulin resistance was carried out as described by Wang et al . [ 42 ] and Gomaa et al[ 43 ] using the homeostatic model assessment of insulin resistance (HOMA-IR) index. The HOMA-IR was calculated according to the following formula: …”
Section: Biochemical Assaymentioning
confidence: 99%
“…Obesity was induced using HFD for 8 weeks, according to the method of Marques et al . with slight modifications and Gomaa et al . The composition of HFD was (wt/wt): 21.2% fat, 49% carbohydrate (34% sucrose plus 15% corn starch), 17.3% protein, 5.0% fibre, 3.5% minerals, 1% vitamin mixture and 3% hydrogenated vegetable oil.…”
Section: Methodsmentioning
confidence: 99%
“…Translational research with "obesogenic" environmental factors such as HFD has shown that animal models play an important role in the identification and testing of cytoprotective compounds for RAT, and this step is essential for identification of targets for pathogenesis-based anti-obesity drugs [24][25][26]. The HFD model, as a high-caloric diet, provides the development of postprandial hyperglycemia that, in turn, promotes excess oxidation caused by nutrients and release of mediators which induce oxidative stress related to metabolic responses [27].…”
Section: Discussionmentioning
confidence: 99%